Effectiveness of Intravenous Ferric Carboxymaltose in the Management of Anemia of Varying Severity in Pregnant Women - Basaran, Ezgi; Guven, Ozge Deniz; Karatas, Esra; Tanacan, Atakan; Sahin, Dilek (Gynecology Obstetrics & Reproductive Medicine, 2025)
Objectives: To evaluate the effectiveness and safety of intravenous ferric carboxymaltose (FCM) in pregnant women with iron deficiency anemia (IDA), comparing outcomes between those with baseline hemoglobin (Hb) levels <8.5 g/dL and ≥8.5 g/dL. The study aimed to assess hematologic response, postpartum anemia rates, and obstetric and neonatal outcomes. Study Design: This retrospective observational study included 161 pregnant women with IDA who received FCM treatment (Hb 7–10 g/dL) between January 2020 and October 2024. Patients were divided into two groups based on initial Hb levels (Group 1: Hb<8.5 g/dL and Group 2: Hb ≥8.5 g/dL). Hematologic parameters were evaluated at baseline, 2 and 4 weeks post-treatment, and postpartum day 1. Obstetric and neonatal outcomes were also compared. Results: Both groups demonstrated significant increases in Hb levels post-treatment (p < 0.001). The increase was more pronounced at 2 and 4 weeks in the group with Hb <8.5 g/dL. At the fourth week after treatment, the increase in hemoglobin levels was 3.36 ± 1.14 g/dL in Group 1, compared to 2.40 ± 0.93 g/dL in Group 2 (all p < 0.001). Postpartum anemia was more common in Group 1 (36.8% vs. 20.3%, p = 0.044), although the absolute Hb gain was greater. There were no serious adverse events, and no statistically significant differences were found in adverse maternal or neonatal outcomes between the groups. Conclusion: Intravenous FCM is an effective and well-tolerated treatment for anemia during pregnancy, providing a rapid rise in Hb levels. The therapy is particularly beneficial for those with more severe anemia, helping to reduce postpartum anemia and potentially improving maternal health outcomes.